Penerapan Reward dalam Meningkatkan Motivasi Belajar pada Kegiatan Pembelajaran Matematika Siswa Kelas IV di MI Islamiyah Babakan - Khalimatus Sadiah (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2022)
This study aims to determine whether giving rewards can increase the learning motivation of fourth grade students of MI Islamiyah Babakan, the method or approach taken in this research is classroom-based research that is qualitative and carried out in the classroom, which is carried out in stages. This type of research is PTK (Classroom Action Research) or Classroom Action Research, with steps of planning, action, observation, and reflection. This research was conducted at Madrasah Ibtidaiyyah Islamiyah Babakan Lebaksiu Tegal, with the research subjects being class IV students in the 2022/2023 academic year totaling 23 students. The results showed that the application of rewarding was effectively used in learning Mathematics, especially fourth grade students of MI Islamiyah Babakan Lebaksiu. This is evidenced by an increase in student learning motivation.